Higher 25‐hydroxyvitamin D levels are associated with greater odds of remission with anti‐tumour necrosis factor‐α medications among patients with inflammatory bowel diseases. Issue 5 (10th January 2017) - Winter, R. W.; Collins, E.; Cao, B.; Carrellas, M.; Crowell, A. M.; Korzenik, J. R.
Summary: Background: Vitamin D has been linked to disease activity among patients with inflammatory bowel diseases (IBD). Prior investigation has also suggested that vitamin D levels may affect duration of therapy with anti‐tumour necrosis factor‐α (anti‐TNF‐α) medications among patients with IBD. Aim: To evaluate the relationship between vitamin D levels and odds of reaching remission while on an anti‐TNF‐α medication. Methods: A total of 521 IBD patients enrolled in the Brigham and Women's IBD Centre database were eligible for inclusion. Patients treated with anti‐TNF‐α therapy who had vitamin D levels drawn within 6 months prior or 2 weeks after initiation of anti‐TNF‐ α medication and who had reported remission status at 3 months were included. A logistic regression model adjusting for age, gender, IBD diagnosis, anti‐TNF‐α medication (infliximab vs. adalimumab) and first or subsequent anti‐TNF‐α medication was used to identify the effect of vitamin D level on initial response to anti‐TNF‐α therapy. Results: A total of 173 patients were included in the final analysis. On logistic regression, patients with normal vitamin D levels n = 122 at the time of anti‐TNF‐ α medication initiation had a 2.64 increased odds of remission at 3 months compared to patients with low vitamin D levels n = 51 when controlling for age, gender, diagnosis, type of anti‐TNF‐α medication and first or subsequent anti‐TNF‐α medication (OR = 2.64, 95% CI = 1.31–5.32, P =  0.0067). Conclusions: These findings suggest that vitamin D levels may influence initial response to anti‐TNF‐ α medication and that low vitamin D levels may pre‐dispose patients to decreased odds of remission. Abstract : Linked Content This article is linked to Hawthorne paper. To view this article visithttps://doi.org/10.1111/apt.13997 .